Peningkatan Pemahaman Mengenai Konsep Keselamatan Kepada Jemaat di GSJA SYALOM Perumnas Pagar Batu - Alma Sari Solin; Delima Manik; Nipa Indra Irawan Waruwu; Adi Suhendra Sigiro (STP Dian Mandala Gunungsitoli Nias Keuskupan Sibolga, 2024)
This research aims to examine how seminars can increase young people's understanding of safety concepts at GSJA SYALOM. This research method uses a case study approach and involves steps such as interviews, observation and documentation. The research results show that seminars can be an effective strategy to increase young people's understanding of safety concepts. Seminars held at GSJA SYALOM help young people understand the meaning and apply the concept of salvation in Christian life. The research results also show that seminars can increase young people's awareness and concern for religious and spiritual values, as well as help them develop a deeper concern for Christian life.